DIVERSIFIKASI OLAHAN HASIL PERIKANAN BERBASIS RUMPUT LAUT DI DESA NURUWE KABUPATEN SERAM BAGIAN BARAT PROVINSI MALUKU - Kaya, Adrianus O W; Loppies, Cindy R M; Lopulalan, Yoisye (Pattimura University, 2022)
Nuruwe Village is one of the centers for producing seaweed in the Western Part of Seram Regency, but it is still limited in products diversifying based on seaweed. This activity aims to provide an understanding and increase the knowledge of the processors in the village of Nuruwe about various types of processed products derived from seaweed. The method of implementing community service activities is counseling and training. Submission of material on the benefits of seaweed and its extraction results as well as applications in the manufacture of food and non-food products. The result of the activity is that the processors are very enthusiastic about the extension activities and the products because they can be directly used and easy to produced